Inappropriate use of calcium supplements among patients with low risk for osteoporosis and its association with knowledge on calcium supplements - Fathima Begum SM,; Hizlinda Tohid,; Teh Rohaila Jamil,; Aida J, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2021)
Calcium supplement use without medical indications may be considered inappropriate as it could cause harms. This study aimed to determine the proportion of individuals with low risk for osteoporosis who used calcium supplements inappropriately. Their practice and factors influencing the use were also examined. This cross-sectional study was conducted at a university-based primary care clinic involving 125 patients, aged 18 to 64 years with low risk for osteoporosis (based on the Osteoporosis Self-assessment Tool for Asians, personal or family history of osteoporosis or hip fracture and diseases of secondary osteoporosis). A validated self-administered questionnaire was used to assess participants’ characteristics, knowledge on calcium supplements (KnowCas-12) and its practice. About 46.4% took calcium supplements within the past one year, whereby many had never discussed the use with doctors (46.6%). However, only 25.9% were compliant and almost all (95%) with incorrect consumption. The two commonest reasons for its use were “to prevent from fracture” (70.7%) and “not enough calcium through my diet” (56.9%). The median (inter quartile range) KnowCas-12 score was 6.0 (3.0) (the possible range: 0-12; the mid-point: 6). Multiple logistic regression showed only KnowCas-12 score had a significant independent association with the use (adjusted odds ratio: 0.79; 95% confidence interval: 0.64-0.98; p=0.031). In conclusion, the inappropriate use of calcium supplements was common among the low-risk individuals, but most were non-compliant with incorrect consumption. Their knowledge of calcium supplements was still lacking. As it could influence the use, educational interventions should be imparted to ensure correct osteoprotective behaviour.